THE EVIDENTIAL STRENGTH OF PSYCHIATRIC VISUM ET REPERTUM IN PROVING THE CRIMINAL ACT OF MOLERGY AGAINST CHILDREN (STUDY OF AMBON DISTRICT COURT DECISION NUMBER: 40/PID.SUS/2019/PN AMB) - Kahfi, Masden; Sugiharto, R. (Jurnal Hukum Khaira Ummah, 2024)
Evidence is an important stage in a trial. With evidence, it can be known whether a defendant can be sentenced because he is proven guilty or acquitted. This study aims to determine, analyze, and provide an overview of the legal force of one of the evidences regulated in Article 184 of the Criminal Procedure Code, namely the Visum et Repertum Psychiatry which is associated with the Study of the Ambon District Court Decision Number: 40 / Pid.Sus / 2019 / PN Amb. The research method used by the Author in this study is Normative Jurisprudence, namely research that uses an approach method to problems by examining the law based on applicable laws and regulations as positive provisions, legal theories, legal concepts, legal principles or can be said by researching and reviewing library materials or secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The results of the study indicate that considering the provisions of Article 183 of the Criminal Procedure Code, the important points are valid evidence and the judge's conviction and at least 2 (two) pieces of evidence are needed, so in the study of the Ambon District Court decision Number: 40 / Pid.Sus / 2019 / PN Amb regarding the crime of child molestation, Visum Et Repertum Psychiatricum is considered necessary to be carried out as evidence and is considered capable of creating a conviction in the judge in his decision, although in practice several obstacles are often encountered. The Public Prosecutor needs to be careful and competent in handling a similar case where if there is no or minimal evidence available, then in the future, Visum et Repertum Psychiatry can be used as evidence that is expected to convince the judge in making a decision.Keywords: Evidence; Visum et Repertum Psychiatry; MolestationAbstractEvidence is an important stage in a court. The existence of evidence determines whether a defendant can be sentenced for being proven guilty or acquitted. This study aims to find out, analyze, and provide an overview of the legal strength of one of the evidence regulated in Article 184 of the Criminal Procedure Code, namely the Psychiatric Visum et Repertum, which is associated with the Study of the Ambon District Court Decision Number: 40/Pid.Sus/2019/PN Amb.The research method used by the author in this research is Normative Juridical, which is a research that uses a method of approaching the problem by examining the law based on applicable laws and regulations as positive provisions, legal theories, legal concepts, legal principles or can be said by examining and examining library materials or secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The results of the study show that considering the provisions in Article 183 of the Criminal Procedure Code, which are important points are valid evidence and the judge's conviction and require at least 2 (two) pieces of evidence, then in the study of the Ambon District Court Decision Number: 40/Pid.Sus/2019/PN Amb regarding the crime of child abuse, the Psychiatric Visum Et Repertum is considered necessary to be carried out to become evidence and is considered capable of causing a conviction in the judge in his decision, although in practice it is often found that there is no evidence to support the decision. The Prosecutor needs to be careful and competent in handling a similar case which if there is no or minimal evidence available, then for the future, a Psychiatric Visum et Repertum can be used as evidence which is expected to convince the judge in making a decision.